Exploration of the effect of botanicals on controlling tea mosquito bug (Helopeltis antonii Signoret) in the cashew ecosystem - Jaya Prabhavathi, S; Senthil Kumar, M; Raja Babu, C; Kalpana, K; Senthilkumar, P; Subrahmaniyan, K; Venkatachalam, S R (Plant Science Today, 2025)
The tea mosquito bug (TMB) Helopeltis antonii Signoret poses a significant threat to cashew plantations, causing substantial damage to the trees and affecting crop productivity. Botanicals have been examined for their effectiveness against tea mosquito bugs (TMB) in cashew plantations that impose damage on cashew trees. A field experiment was conducted at the Regional Research Station, Vridhachalam, Tamil Nadu, to evaluate the effectiveness of various botanical pesticides against TMB. The study included seven treatments using different botanicals and one untreated control. Applications were made at critical growth stages, namely flushing, flowering and nut formation, at fortnightly intervals, ensuring the pest population remained below the economic threshold level (ETL). Five spray rounds were administered, with a maximum of 10 L of spray suspension applied per tree for each treatment. The results demonstrated a significant reduction in TMB incidence in plots treated with botanical pesticides. Fifteen days after the third, fourth and fifth sprays, TMB incidence was completely absent in treated plots, whereas the untreated control recorded a damage score of 3.25. Furthermore, a marked decline in fresh TMB infestations was observed within seven days following each spray application. Among the treatments, a mixture of leaf extracts from adathoda (Adathoda vasica), datura (Datura metel), vitex (Vitex negundo), calotropis (Calotropis gigantea) and neem (Azadirachta indica) showed the highest efficacy, reducing TMB incidence to damage scales of 0.660 and 0.550. Similarly, Pongamia oil (5 % concentration) exhibited substantial effectiveness, reducing TMB incidence to scales of 0.845 and 0.645. These findings highlight the potential of botanical pesticides as eco–friendly and effective alternatives for managing TMB in cashew plantations.